Gaining Teachers' Insights: School Library Access and Its Significance on Science and Mathematics Education - Lulama Mdodana-Zide (Indonesia Approach Education, 2024)
Access to libraries significantly enhances Science and Mathematics education, offering diverse pathways for learners to engage with concepts using media and digital literacy skills. However, the contribution of school libraries to these subjects remains unexplored despite attention to learners and Science, Technology, Engineering and Mathematics education. This study examined insights from Science and Mathematics teachers regarding the role of library resources, such as books, research materials, and interactive tools, in supporting students' comprehension, critical thinking, and problem-solving skills in these subjects. Employing a qualitative approach within an interpretive paradigm, the research used a multiple-case study design. Data collection involved questionnaires administered to 12 teachers from six purposefully selected schools. Findings indicated that school library access positively impacts student engagement in Science and Mathematics education as resources facilitate better understanding and application of concepts, encourage independent exploration, nurture inquiry-based learning, act as bridges in the integration of subjects, mitigate resource disparities, and provide teacher professional development. The study concludes by not only advocating a heightened prominence on library access in schools but also positions the teachers as key elements in channeling learners toward the use of these invaluable informative hubs to shape the landscape of Science and Mathematics education. Thus, the study opens the door for a paradigm shift toward the optimization of library access for all learners to harness the unrealized potential within the pages and digital interfaces of school libraries by illuminating the transformational significance of libraries in Science and Mathematics.